Staging national identities in contemporary Estonian theatre and film - Võsu, Ester; Joosepson, Alo (Sign Systems Studies, 2005)
This paper focuses on the ways in which national identities are staged in recent film and theatre productions in Estonia. We want to complement the prevalent approaches to nationality (Anderson 1983; Gellner 1983; Bhabha 1990), where the role of theatre and film as modellers of national identity are undervalued. National identity is a complex term that presupposes some clarification, which we gave by describing its dynamics today; its relation to ethnic identity, a thread between the lived and declared national identities, and the relevance of culture-based national identity. Herein we consider the concept of staging to have two implications: (1) as an aesthetic term it incorporates an artistic process, comprising several devices and levels; (2) as a concept in cultural theory it describes cultural processes in which something is set on stage for public reflection. Accordingly, in our analysis we considered national identities in theatre and film stagings in both senses. The results of our analyses demonstrated that our hypothesis about emerging new national identities in Estonia was valid, though deconstructed and hybrid national identities are not exactly and absolutely new types of identities but rather strategies of creating space for new identities to develop. A deconstructed national identity refers to the state of high self-reflexivity in which the existing elements of national identity are re-examined, recontextualised and re-evaluated. Further, a hybrid national identity demonstrates the diversity and coexistence of the components of national identity. Both strategies of staging are characteristic of the transformation of national identities, confirming that a single homogenous staging of national identity seems to be replaced by bringing multiple new self-models on stage.